Climate Change, Conflict, and Cooperation : Global Analysis of the Resilience of International River Treaties to Increased Water Variability - Dinar, Shlomi; Katz, David; De Stefano, Lucia; Blankespoor, Brian (World Bank, Washington, DC, 2014)
Although water variability has already been observed across river basins, climate change is predicted to increase variability. Such environmental changes may aggravate political tensions, especially in regions that are not equipped with an appropriate institutional apparatus. Increased variability is also likely to challenge regions with existing institutional capacity. This paper argues that the best attempts to assess the ability of states to deal with variability in the future rest with considering how agreements have fared in the past. The paper investigates to what extent particular mechanisms and institutional designs help mitigate inter-country tensions over shared water. The analysis specifically focuses on identifying which water allocation mechanisms and institutional features provide better opportunities for mitigating conflict given that water allocation issues tend to be most salient among riparians. Water-related events from the Basins at Risk events database are used as the dependent variable to test hypotheses regarding the viability, or resilience, of treaties over time. Climatic, geographic, political, and economic variables are used as controls. The analysis is conducted for the years 1948-2001 with the country dyad as the level of observation. Findings pertaining to the primary explanatory variables suggest that country dyads governed by treaties with water allocation mechanisms exhibiting both flexibility and specificity evince more cooperative behavior. Country dyads governed by treaties with a larger sum of institutional mechanisms likewise evince a higher level of cooperation, although certain institutional mechanisms are more important than others.